From debris to wealth?: Paradoxes of sustainability from india’s breadbasket = ¿De los residuos a la riqueza? Paradojas de la sostenibilidad en el granero de la India - Bonfanti, Sara (Vergentis, 2024)
The article traces an emblematic case study of the ecological transition in the South: the attempt to abandon the practice of stubble burning, or the burning of crop residues, in the Punjab region, ‘the granary of India’. This procedure, traditionally used by farmers to prepare fields for subsequent sowing, has recently been banned by the central Indian state due to its negative impact on air pollution, soil degradation, and public health. Alternative crop residue management systems (composting, incorporation into the soil as fertiliser, recycling as feed, and use in biogas production) have been initiated. However, the transition presents considerable challenges, especially for local communities, which are often in poverty and struggle to adapt to the new agricultural policies. Beyond populist media accusations and repressive legislation, the encounter with smallholder farmers calls for a holistic understanding of the socio-economic and cultural dynamics at work in Punjab, revealing the paradoxes of sustainability and pointing to a more just but still unexplored path of ecological transition that can also be applied in other rural contexts, not only limited but inspired by restorative wisdom in South Asia.